University social responsibility: Challenging systemic racism in the aftermath of George Floyd's murder - Paulette A. Meikle; Lekeitha R. Morris (Administrative Sciences, 2022)
In this paper, we examine university discretionary interpretation of the 2020 social upheaval that emanated from George Floyd's murder as an element of university social responsibility (USR) policymaking. The paper addresses two research questions: (a) What are university presidents' implicit and explicit social justice responses to George Floyd's death and the idealistic protests of 2020? (b) To what degree are principles of social justice embedded in universities' intellectual roots and social responsibility? Using a sample of university presidents' public statements in response to George Floyd's death and the idealistic protests of 2020, we analyze the response and responsibilities of universities in the struggle for a just society. We cross-check mission statements and strategic plans to corroborate universities' public statements with their institutional philosophies, mission, and action plans relating to discrimination against racial and ethnic minorities and systemic racism. We use critical discourse analysis and the Voyant Tool to perform a textual analysis of 62 university presidents' letters and mission statements. They all denounced the dehumanization and inequitable treatment of Black people. An important implication of our work is the sharp difference in the depth and forthrightness of responses by university presidents across university types. Some presidential letters are forthright in their denouncement of the murder of George Floyd and systemic racism, while others were, at best, vague in their approach. Presidential letters disclose their institutions' priorities, organizational identities, and social responsibility convictions. Overall, mission statements and strategic plans included addressing systemic racism and inequality. While there is no ordered symmetry between presidential narratives and institutional action, we anticipate social responsibility as a core institutional value. We argue for social justice anti-racist platforms as critical dimensions of USR. We call for university milieus that promote a fair and just society among all stakeholders.
Keywords: 350; social justice; university leadership; university social responsibility